HUBUNGAN KEKERUHAN, pH DAN SUHU TERHADAP KONSENTRASI LOGAM BERAT PADA AIR SUNGAI DI TANGERANG - Diana Rinawati; Nurmeily Rachmawati; Istiana Annisa; Meilina Meilina (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2022)
Rapid industrial growth can cause environmental pollution if not balanced with good environmentalmanagement. To determine the concentration of heavy metals in polluted water, it is better tomeasure turbidity, pH and temperature as other factors in determining the concentration of heavymetals in water bodies. For this reason, it is necessary to know the relationship between turbidity,pH, temperature and the concentration of heavy metals (Pb, Cd, Hg) in river water in Tangerang.The design of this study is a descriptive correlational study, with a total sample of 36 samples ofCirarab, Cimanceuri, Cidurian and Cisadane rivers in kabupaten Tangerang. The sample pointsare on the left, middle and right of the river with measurement times in the morning, afternoon andevening. Examination of Pb and Cd using a Non-flame Atomic Absorption Spectrophotometer(Graphite Furnace AAS). While for Hg using a Mercury Analyzer. The working principle of the AASfurnace is the process of breaking molecules into atoms using electricity. The working principle ofthe Hg probe is the process of breaking molecules into atoms using cold steam. The results showedthat the concentrations of Mercury and Cadmium were both below the quality standard with a valueof 10-4 (0.0002 mg/L). Lead concentrations varied mostly below the quality standard (0.03 mg/L).pH, temperature according to environmental conditions and turbidity below the quality standard.(400 NTU) The results of statistical tests with P values of 0.571, 0.440, 0864. It was obtained thatthere was no relationship between turbidity, pH and temperature with the concentration of Lead.The conclusion is that there is no relationship between turbidity, temperature, pH with heavy metalconcentrations expecially Lead in rivers in kabupaten Tangerang.